2022
DOI: 10.1038/s12276-022-00796-y
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase 3 promotes alveolar epithelial–mesenchymal transition and fibroblast migration under hypoxic conditions

Abstract: Epithelial–mesenchymal transition (EMT), a process by which epithelial cells undergo a phenotypic conversion that leads to myofibroblast formation, plays a crucial role in the progression of idiopathic pulmonary fibrosis (IPF). Recently, it was revealed that hypoxia promotes alveolar EMT and that histone deacetylases (HDACs) are abnormally overexpressed in the lung tissues of IPF patients. In this study, we showed that HDAC3 regulated alveolar EMT markers via the AKT pathway during hypoxia and that inhibition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Another study reported that treatment with EZH2 inhibitors could suppress M1 macrophages while promoting M2 macrophage differentiation by activating peroxisome proliferator-activated receptor ( PPAR )-γ and modulating the signal transducer and activator of transcription/ suppressor of cytokine signaling ( STAT / SOCS ) pathway ( 61 ). MicroRNA-224 ( miR - 224 ) and its target forkhead box A1 ( FOXA1 ) inhibit the expression of EMT markers and the migration and invasion of human lung fibroblasts in IPF under hypoxia ( 62 ). Bromodomain containing 4 ( BRD4 ) plays a critical role in promoting pulmonary myofibroblast activation and redox imbalance, and BRD4 inhibitors is capable of inhibiting the profibrotic effects of IPF and attenuates bleomycin-induced lung fibrosis in mice ( 63 , 64 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported that treatment with EZH2 inhibitors could suppress M1 macrophages while promoting M2 macrophage differentiation by activating peroxisome proliferator-activated receptor ( PPAR )-γ and modulating the signal transducer and activator of transcription/ suppressor of cytokine signaling ( STAT / SOCS ) pathway ( 61 ). MicroRNA-224 ( miR - 224 ) and its target forkhead box A1 ( FOXA1 ) inhibit the expression of EMT markers and the migration and invasion of human lung fibroblasts in IPF under hypoxia ( 62 ). Bromodomain containing 4 ( BRD4 ) plays a critical role in promoting pulmonary myofibroblast activation and redox imbalance, and BRD4 inhibitors is capable of inhibiting the profibrotic effects of IPF and attenuates bleomycin-induced lung fibrosis in mice ( 63 , 64 ).…”
Section: Discussionmentioning
confidence: 99%
“…HDAC3 significantly increased Snail expression under hypoxic conditions, and this effect was prevented by inhibition of Hypoxia-inducible factor 1-alpha (HIF1 α), a subunit of a heterodimeric transcription factor hypoxia-inducible factor 1 ( HIF-1 ). HDAC3 increases the transcriptional activity of HIF-1α by promoting the binding of HIF-1α to the hypoxia-responsive element (HRE) sites of genes [ 129 ]. Since fibroblast migration is considered a critical contributor to lung fibrosis, it was recently demonstrated that HDAC3-miR224- Forkhead Box A1 (FOXA1) axis effectively regulated the migration and invasion of fibroblast cells under hypoxia [ 129 ].…”
Section: Epigenetics Regulation Of Emp/emt-dependent Fibrosismentioning
confidence: 99%
“…HDAC3 increases the transcriptional activity of HIF-1α by promoting the binding of HIF-1α to the hypoxia-responsive element (HRE) sites of genes [ 129 ]. Since fibroblast migration is considered a critical contributor to lung fibrosis, it was recently demonstrated that HDAC3-miR224- Forkhead Box A1 (FOXA1) axis effectively regulated the migration and invasion of fibroblast cells under hypoxia [ 129 ]. The effective involvement of HDAC3 in EMT-dependent fibrosis in lung was demonstrated by the use of HDAC3 siRNA that alleviated BLM-induced pulmonary fibrosis in mice.…”
Section: Epigenetics Regulation Of Emp/emt-dependent Fibrosismentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, pharmacologic inhibition of class I HDACs via SAHA or MS275 in the context of diabetes and obesity enhanced mitochondrial function as well as oxidative capacity in adipose tissue and skeletal muscle [ 24 ]. Under hypoxic conditions, HDAC3 accelerated the progression of pulmonary fibrosis by promoting epithelial-mesenchymal transition in alveolar epithelial cells [ 25 ]. However, it remains unknown whether HDAC3 deletion could attenuate LPS-induced ALI and epithelial barrier dysfunction by modulating MQC in alveolar epithelial cells.…”
Section: Introductionmentioning
confidence: 99%